Design and maintenance of medical oxygen concentrators in Sub-Saharan Africa: a systematic review - Nahimiya Husen Ibrahim; James Wallace; Davide Piaggio; Leandro Pecchia (BMC Health Services Research)
Abstract Background Oxygen therapy is critical and vital treatment for hypoxemia and respiratory distress, however, access to reliable oxygen systems remains limited in SSA. Despite WHO initiatives that distributed over 30,000 OC oxygen concentrators worldwide, SSA faces significant challenges related to their maintenance and use, due to harsh environmental conditions, technical skill shortages and inadequate infrastructure. This review aims to systematically identify and assess the literature on OC design adaptations, maintenance challenges, and knowledge gaps in SSA, providing actionable recommendations to inform innovative and context-sensitive solutions to improve healthcare delivery in the region. Methods The study focused on medical oxygen concentrators in SSA countries. It was conducted by following the PRISMA statement and searching three databases, i.e., Scopus, PubMed, and Web of Science, for publications in the period 2001–2023, using the search terms: oxygen concentrator, therapy, cylinder, plant, supply, delivery, and availability, design, and maintenance. The screening process involved evaluating manuscripts based on their titles, abstracts and full texts, based on specific inclusion and exclusion criteria. The extracted information included the author’s publication year, country, study aim, and key findings. Results Overall, 1,057 papers were returned for our analysis, of which 20 met the inclusion criteria. These studies primarily examined the design, availability and cost-effectiveness of oxygen concentrators compared to cylinders, revealing a significant supply and demand gap for these devices in SSA. It also illustrated how the environmental challenges impacted the devices durability, highlighting the need for more locally adapted resilient solutions. Solar-powered systems provide a sustainable option in areas with unstable power supplies, although initial costs remain high. Robust maintenance strategies, capacity building and strict procurement protocols proved essential to ensuring equipment long-term functionality. Conclusion This review synthesized and critically assessed the current in the body of literature, enabling highlighting valuable insights for innovators and stakeholders with an interest in enhancing the oxygen availability in SSA. It highlighted a pressing need for improved healthcare infrastructure investment, context-aware OC design and novel standards and regulatory frameworks to support frugal innovation.